## Access

You are not currently logged in.

Access JSTOR through your library or other institution:

## If You Use a Screen Reader

This content is available through Read Online (Free) program, which relies on page scans. Since scans are not currently available to screen readers, please contact JSTOR User Support for access. We'll provide a PDF copy for your screen reader.
Journal Article

# Orthogonal Polynomials Arising in the Numerical Evaluation of Inverse Laplace Transforms

Herbert E. Salzer
Mathematical Tables and Other Aids to Computation
Vol. 9, No. 52 (Oct., 1955), pp. 164-177
DOI: 10.2307/2002053
Stable URL: http://www.jstor.org/stable/2002053
Page Count: 14

#### Select the topics that are inaccurate.

Cancel
Preview not available

## Abstract

In finding f(t), the inverse LAPLACE transform of F(p), where (1) f(t) = (1/2π j) ∫c+j∞c-j∞ eptF(p)dp, the function F(p) may be either known only numerical or too complicated for evaluating f(t) by CAUCHY's theorem. When F(p) behaves like a polynomial without a constant term, in the variable 1/p, along (c - j∞, c + j∞), one may find f(t) numerically using new quadrature formulas (analogous to those employing the zeros of the LAGUERRE polynomials in the direct Laplace transform). Suitable choice of pi yields an n-point quadrature formula that is exact when ρ2n is any arbitrary polynomial of the (2n)th degree in $x \equiv 1/p$ without a constant term, namely: (2) (1/2π j) ∫c+j∞c-j∞ ep ρ2n(1/p)dp = ∑i=1n Ai(n) ρ2n(1/pi). In (2), $x_i \equiv 1/p_i$ are the zeros of the orthogonal polynomials $p_n(x) \equiv 1/p_i$ are the zeros of the orthogonal polynomials $p_n(x) \equiv \Pi^n_{i=1} (x - x_i)$ where (3) (1/2π j) ∫c+j∞c-j∞ ep(1/p)pn(1/p)(1/p)idp = 0, i = 0, 1, ⋯, n - 1 and Ai(n) correspond to the CHRISTOFFEL numbers. The normalization $P_n(1/p) \equiv (4n - 2)(4n - 6) \cdots 6p_n(1/p), n \geq 2$, produces all integral coeffients. Pn(1/p) is proven to be (-1)n e-ppndn(ep/pn)/dpn. The normalization factor is proved, in three different ways, to be given by (4) (1/2π j) ∫c+j∞c-j∞ ep(1/p)[ Pn(1/p) ]2dp = 1/2(-1)n. Proofs are given for the recurrence formula (5) (2n - 3)Pn(x) = [ (4n - 2)(2n - 3)x + 2 ] Pn-1(x) + (2n - 1)Pn-2(x), for n ≥ 3, and the differential equation (6) x2Pn"(x) + (x - 1)Pn'(x) - n2Pn(x) = 0. The quantities pi(n), 1/pi(n) and Ai(n) were computed, mostly to 6S - 8S, for i = 1(1)n, n = 1(1)8.

• 164
• 165
• 166
• 167
• 168
• 169
• 170
• 171
• 172
• 173
• 174
• 175
• 176
• 177